Formation of Market Values in the Development of Modern Theatrical Art - Orlova, Olha I.; Орлова, Ольга Іванівна (My University, 2016)
The current state of Performing Arts in Ukraine shows two challenging trends that form the main contradiction of society spiritual development – a deepening spirituality of society and commercialization of art and cultural sphere. At the same time modern Ukrainian culture and theatre in particular, act as a significant factor further political transformations in Ukraine, because the theatre as a social institution, forming public opinion, which is a tool of influence on the political consciousness of the electorate. The modern theatrical art is need other important social functions – spiritual, educational, informative and more. Making of these functions determines the ability of Ukrainian culture despite its excessive commercialization, to become a powerful stimulus for further political transformations in the Ukrainian society. In this article the analysis of functional and institutional capabilities of modern Ukrainian theatre as an important element of the cultural sphere shape market values in the social environment, overcoming the traditional dependence of the electorate from the manipulative influence of political groups. Striking evidence of the growing capacity of theatre in modern conditions is the activization and the impetuous development of new theatre trends on the basis of upholding the ideals of freedom and fairness. The development of modern theatrical currents determine the trends of theatre in the near future and the determination of the political process demonstrates the nature of the cultural interaction between the community members, aimed at upholding the ideals of democracy. Формування ринкових цінностей – одна з інституційних функцій сучасного театрального мистецтва. У статті проаналізовано функції сучасного українського театру як важливого елемента системи духовного виробництва, інструменту формування цінностей суспільства з ринковою економікою. Яскраве свідчення зростаючого потенціалу театру в сучасних умовах – активізація та стрімкий розвиток нових тенденцій у театральному середовищі на основі відстоювання ідеалів свободи й справедливості. Такі тенденції визначатимуть логіку розвитку театру як соціального інституту в найближчому майбутньому.
Формування ринкових цінностей у розвитку сучасного театрального мистецтва
Keywords: theatre; spiritual production; market values; technology; theatrical process; театр; духовне виробництво; ринкові цінності; технології; театральний процес